On the importance of stochasticity of composite workpiece structures for post-processing operations: An analysis of errors on fixturing problems. (15th October 2021) - Gameros, A.; Diaz, O. Gavalda; Axinte, D.; Novovic, D.
Abstract: As woven composites have attracted the attention of high-value industries, their broader implementation should be supported by an enhanced understating of the impact that their characteristic uneven surface has on high-precision post-processing operations (e.g. machining). Here, this gap is addressed by analysing the positioning error (i.e. linear/angular deviations from a reference) of woven composite workpieces prior post-processing operations. A bespoke model, tailored to simulate large stochastic surfaces, is presented and employed to construct several realistic "virtual workpieces" to study the interactions between the woven surface of the composite and the locating elements of a work-holding fixture. Results show that positioning errors are considerably reduced by improving the fixture's geometric design, highlighting for the first time the crucial effect that the workpiece's uneven surface has on post-processing operations. The versatility of the model allows its use on other applications where understanding this effect is critical (e.g. gripping during mechanical testing).